2018
DOI: 10.21037/jtd.2018.05.26
|View full text |Cite
|
Sign up to set email alerts
|

A predictor for mitral valve repair in patient with rheumatic heart disease: the bending angle of anterior mitral leaflet

Abstract: The bending angle of AML which was considered as quantification of mobility and flexibility of AML can be a predictor for MV repair in patients with rheumatic heart disease (RHD). The small single area of commissural calcification had no effect on reparability of rheumatic MV disease. WS cannot appropriately predict the outcome of rheumatic MV repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The details for echocardiographic measurements in routine clinical practice were described in our previous studies. 10,11)…”
Section: Echocardiographymentioning
confidence: 99%
“…The details for echocardiographic measurements in routine clinical practice were described in our previous studies. 10,11)…”
Section: Echocardiographymentioning
confidence: 99%
“…A report from China cited anterior leaflet flexibility as important in assessing repairability, utilizing the bending angle of the anterior leaflet (eg, a surrogate for rigidity/ flexibility) to predict repair suitability reasonably well in a Chinese population. 24 Indian researchers found anterior leaflet length ≥26 mm (indexed length, 18 mm/m 2 ) to be associated with successful repair. 25 However, many of these assessments were performed in developing nations, in which pure MR and mixed lesions are more common than MS, which is more commonly seen in the older US population.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the adoption of mitral repair for rheumatic valve disease, techniques need to be made more reproducible and results followed up. This can be achieved by identifying selection criteria for repair candidates ( [91][92][93], standardizing a methodical approach to rheumatic mitral valve repair which can be taught and audited (88,94,95) and, importantly, strengthening local surgical programs in endemic areas, with expert valve repair surgeons providing technical guidance as well as mentorship on systematic follow-up and audit (90,96). Collaboration of local surgical programs, through mutual site visits, workshops, or regional meetings, can have a significant effect on the wide adoption of rheumatic valve repair and the improvement of its techniques.…”
Section: "Conduct Studies That Determine the Potential Valuementioning
confidence: 99%
“…A number of reports regarding surgery for rheumatic valve disease have been published recently, mostly from Asia. Fu and colleagues from Beijing, China have published their own experience (93), as well as a metanalysis (88), comparing outcomes between repair and replacement. They concluded that the repair group had better early mortality and less valve related events with similar reoperation rates.…”
Section: "Conduct Studies That Determine the Potential Valuementioning
confidence: 99%